2002
DOI: 10.1162/089892902317361877
|View full text |Cite
|
Sign up to set email alerts
|

The Psychophysiology of Real-Time Financial Risk Processing

Abstract: A longstanding controversy in economics and finance is whether financial markets are governed by rational forces or by emotional responses. We study the importance of emotion in the decision-making process of professional securities traders by measuring their physiological characteristics (e.g., skin conductance, blood volume pulse, etc.) during live trading sessions while simultaneously capturing real-time prices from which market events can be detected. In a sample of 10 traders, we find statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(120 citation statements)
references
References 31 publications
(28 reference statements)
8
101
1
1
Order By: Relevance
“…For example, a field study of 10 traders showed a significant relationship between volatility and skin conductance and heart rate (Lo & Repin, 2002); another study of real-time changes in traders hormones showed increases in market 9 volatility to predict increases in levels of cortisol; a hormone related to fear response (Coates & Herbert, 2008). We would thus expect that traders will face greater difficulty in regulating emotions during periods of high market volatility.…”
Section: H1: Moment By Moment Regulation Of Emotions During Trading Amentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a field study of 10 traders showed a significant relationship between volatility and skin conductance and heart rate (Lo & Repin, 2002); another study of real-time changes in traders hormones showed increases in market 9 volatility to predict increases in levels of cortisol; a hormone related to fear response (Coates & Herbert, 2008). We would thus expect that traders will face greater difficulty in regulating emotions during periods of high market volatility.…”
Section: H1: Moment By Moment Regulation Of Emotions During Trading Amentioning
confidence: 99%
“…Seo and Barrett (2007) found investment club members who regulated emotions more effectively (as measured by greater discrimination between discrete emotions) to perform more effectively in a trading simulation. In a physiological study of 10 traders, Lo and Repin found evidence of emotion-related physiological reactions to trading events but less intense reactions among more experienced than less experienced traders (Lo & Repin, 2002). However, much emotion regulation is inaccessible to self-report.…”
Section: The Role Of Emotion Regulationmentioning
confidence: 99%
“…However, direct risk prediction has been shown to be reflected in the bodily states of professional financial traders (Lo and Repin, 2002). In addition, recent behavioral evidence shows that human subjects adjust their learning rate to changing risk, implying that they must somehow be tracking risk (Behrens et al, 2007;Preuschoff and Bossaerts, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore decided to conduct the study on a real trading floor rather than under laboratory conditions and to sample steroids while traders did their normal jobs (9). With permission from the managers of a midsized trading floor (Ϸ260 traders, of which 4 were female) in the City of London, we recruited 17 male traders to participate in the study.…”
mentioning
confidence: 99%